Thermal tolerance and acclimation limits in bull trout ( Salvelinus confluentus ) alevin - Brendan Maldonado; Travis Durhack; Andrew Chapelsky; Sarah E. Glowa; Analisa Lazaro‐Côté; Raven M. Bennett; Timothy Bartley; Neil J. Mochnacz (Journal of Fish Biology, 2026)
The critical thermal maximum ( CT max ) of bull trout ( Salvelinus confluentus ) alevin was measured after 3 weeks of acclimation to 4–21°C. CT max increased from 24.3 at 4°C to 26.7 at 9°C, plateaued between 9 and 12°C (26.9°C), and declined to 25.9°C at 15°C. Acclimation mortality increased above 12°C, reaching 53.7% at 15°C, and no fish survived at 18–21°C. Condition factor declined at ≥12°C. Results indicate bull trout alevin have limited acclimation capacity beyond 12°C and suggest high vulnerability to lethal stress in streams where temperatures exceed this threshold.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Organic solutes in the deepest phylogenetic branches of the Bacteria: identification of α(1–6)glucosyl-α(1–2)glucosylglycerate in Persephonella marina - Pedro Lamosa; Marta V. Rodrigues; Luís G. Gonçalves; Jean Carr; Rita Ventura; Christopher Maycock; Neil D. Raven; Helena Santos (Extremophiles, 2013)

Comparative study of the thermostabilizing properties of mannosylglycerate and other compatible solutes on model enzymes - Nuno Borges; Ana Ramos; Neil Raven; Richard Sharp; Helena Santos (Extremophiles, 2002)

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)